2014
DOI: 10.4161/rna.28353
|View full text |Cite
|
Sign up to set email alerts
|

Novel regulatory principles of the spliceosomal Brr2 RNA helicase and links to retinal disease in humans

Abstract: For each round of pre-mRNA splicing, a spliceosome is assembled anew on its substrate. RNA-protein remodeling events required for spliceosome assembly, splicing catalysis, and spliceosome disassembly are driven and controlled by a conserved group of ATPases/RNA helicases. The activities of most of these enzymes are timed by their recruitment to the spliceosome. The Brr2 enzyme, however, which mediates spliceosome catalytic activation, is a stable subunit of the spliceosome, and thus, requires special regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 72 publications
(126 reference statements)
3
52
0
Order By: Relevance
“…Fine-tuning of the binding strength of the Jab1 C-terminal tail to the Brr2 RNAbinding tunnel likely relies on the intrinsically unstructured nature of this tail. 88 Taken together, presently available structures of isolated Brr2-Jab1 complexes, tri-snRNPs and spliceosomes in combination with functional studies support the notion that the NTR is essential to shut off Brr2 activity during tri-snRNP assembly and during several stages of splicing, and that the Jab1 domain remains stably bound to Brr2 during all phases of splicing, in which Brr2 is present (Fig. 1).…”
Section: Brr2 Regulation During Splicingsupporting
confidence: 63%
See 2 more Smart Citations
“…Fine-tuning of the binding strength of the Jab1 C-terminal tail to the Brr2 RNAbinding tunnel likely relies on the intrinsically unstructured nature of this tail. 88 Taken together, presently available structures of isolated Brr2-Jab1 complexes, tri-snRNPs and spliceosomes in combination with functional studies support the notion that the NTR is essential to shut off Brr2 activity during tri-snRNP assembly and during several stages of splicing, and that the Jab1 domain remains stably bound to Brr2 during all phases of splicing, in which Brr2 is present (Fig. 1).…”
Section: Brr2 Regulation During Splicingsupporting
confidence: 63%
“…53,56 The functional relevance of this mode of Brr2 inhibition is underscored by the observation that mutations in Prp8, which affect residues in the Jab1 C-terminal tail and interfere with its function, lead to a severe form of retinitis pigmentosa in human. 53,88 The tail insertion was first observed in the structure of a human Brr2-Jab1 complex, 53 in which the Brr2 subunit lacked all elements of the NTR except the NC-clamp, but was not seen in a slightly further truncated yeast Brr2-Jab1 complex. 38 These findings raised the question whether the Jab1 tail insertion is conserved among organisms.…”
Section: Brr2 Regulation Via Trans-acting Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…This is an interesting result, as Brr2 is expected to unwind U4/U6 in the context of the trisnRNP (Laggerbauer et al 1998;Raghunathan and Guthrie 1998), dissociating it into three individual snRNPs (free U4, U5, and U6), and suggests that more is required to activate Brr2 to unwind U4/U6. Thus, it is likely that, though the binding affinity between Brr2 and the Prp8 Jab1/MPN domain is high (Mozaffari-Jovin et al 2014), the Prp8 Jab1/MPN tail can dissociate from the Brr2 RNA binding pocket upon minute conformational changes. This is consistent with a previous Brr2 Prp8 Jab1/MPN domain co-crystal (Nguyen et al 2013), where the density corresponding to the Prp8 Jab1/MPN tail is absent.…”
Section: Characterization Of a Prp8-rp Splicing Defectmentioning
confidence: 99%
“…Later biochemical studies revealed that the Prp8 Jab1/MPN domain also stimulates Brr2 helicase activity while suppressing Brr2 ATPase activity (Pena et al 2007;Maeder et al 2009;Mozaffari-Jovin et al 2014). Further studies have revealed additional complexity.…”
Section: Introductionmentioning
confidence: 99%